An inner filter effect based sensor of tetracycline hydrochloride as developed by loading photoluminescent carbon nanodots in the electrospun nanofibers. Issue 5 (19th January 2016) - Lin, Min; Zou, Hong Yan; Yang, Tong; Liu, Ze Xi; Liu, Hui; Huang, Cheng Zhi
Abstract : Highly photoluminescent carbon nanodots (CDs), which have been loaded in the electrospun nanofibers, are applied to develop an IFE-based visual sensor for tetracycline hydrochloride (Tc) sensing in milk. Abstract : The inner filter effect (IFE), which results from the absorption of the excitation or emission light by absorbers, has been employed as an alternative approach in sensing systems due to its flexibility and simplicity. In this work, highly photoluminescent carbon nanodots (CDs), which were simply prepared through a new one-step microwave synthesis route, were loaded in electrospun nanofibers, and the obtained nanofibers were then successfully applied to develop a fluorescent IFE-based visual sensor for tetracycline hydrochloride (Tc) sensing in milk. This developed visual sensor has high selectivity owing to the requirements of the spectral overlap between the CDs and Tc, showing high promise in sensing chemistry with an efficient response and economic effect.